Micro-nutrient Contents of Field Grown Seedlings, Saplings and Trees of a Mangrove Species, Bruguiera parviflora (Wight & Arnold) in the Kuala Selangor Nature Park, Malaysia - Hossain, Mahmood; Othman, Saberi (Indian Forester, 2007)
Micronutrients (Cu, Fe and Zn) content in different components of seedlings, saplings and trees were analyzed for field grown Bruguiera parviflora at Kuala Selangor Nature Park mangrove forest, Malaysia. A relatively higher copper content of 17.87 Î¼g g-1 was observed in stems of seedlings followed by branches and roots of saplings and trees. Comparatively higher iron content of 5263.47- 6310.40 Î¼g g-1 was found in roots of seedlings, saplings and trees. While, higher zinc content of 35.47 Î¼g g-1 and 29.60 Î¼g g-1 were detected in leaves of seedlings and roots of saplings, respectively. Copper, iron and zinc content showed different distributional trends among seedling and tree components, while iron and zinc showed similar trend in saplings components.